Effect of oil content of sunflower seeds on the equilibrium moisture relationship and the safe storage condition - Maciel, Gisele; De La Torre, Diego; Izquierdo, Natalia Gabriela; Cendoya, María Gabriela; Bartosik, Ricardo Enrique (International Commission of Agricultural and Biosystems Engineering, 2017)
The adsorption and desorption equilibrium moisture content/equilibrium relative humidity relationships of sunflower seeds with four different oil contents (35.7%, 44.6%, 48.6% and 52.7%) were obtained for temperatures of 8, 15, 25 and 35°C and moisture contents of 6.0%, 8.5%, 11.0%, 13.5%, 16.0% and 18.5%.The goodness of fit of four equilibrium moisture content/equilibrium relative humidity models (Modified Henderson, Modified Chung-Pfost, Modified Halsey and Modified Oswin) were evaluated for each oil content. The Modified Halsey model was the best for predicting equilibrium moisture content/equilibrium relative humidity relationships based on the Akaike Information Criterion, the Bayesian Information Criterion and estimated residual standard deviation. The optimized parameters for the Modified Halsey model are presented for each oil content. Results indicate that the oil content substantially affected the equilibrium moisture content/equilibrium relative humidity relationship. As the oil content increases, the equilibrium relative humidity also increases for the same moisture content, meaning that to use the right set of parameters according to the oil content of the hybrids is critical for sunflower drying, conditioning and storing. The safe storage moisture content varied from 12.0% to 7.6% for seeds with oil contents from 35.7% to 52.7%, implying that a revision of the sunflower market moisture content might be required for safe storage of hybrids with high oil content.